Chitotriosidase enzyme activity: is this a possible chronic inflammation marker in children with common variable immunodeficiency and early atherosclerosis?. (November 2017) - Azarsız, Elif; Karaca, Neslihan; Levent, Erturk; Kutukculer, Necil; Sozmen, Eser
Background: Common variable immunodeficiency is a rare clinically symptomatic primary immunodeficiency disorder which manifests a wide variability of symptoms, complications. Atherosclerosis in common variable immunodeficiency patients has not been investigated yet contrary to other severe clinical complications. We aimed to investigate the chitotriosidase enzyme's role as an inflammation and atherosclerosis marker in paediatric common variable immunodeficiency patients. Methods: Common variable immunodeficiency patients (n = 24) and healthy controls (n = 23) evaluated for chitotriosidase activity with other inflammation markers (hsCRP, myeloperoxidase, serum amyloid A, ferritin), lipid profile and echocardiographic findings (carotid artery intima media thickness – cIMT, brachial artery flow-mediated vazodilatation – FMD%). Results: In patients, the mean chitotriosidase activity (8.98 ± 6.28) was significantly higher than the controls (5.17 ± 3.42) ( P = 0.014). Chitotriosidase showed positive relation with hs-CRP ( P = 0.011) and SAA ( P = 0.011) but had no relation with ferritin ( P = 0.155), HDL ( P = 0.152) or LDL-cholesterol ( P = 0.380). Mean cIMT increased in patients compared with the controls ( P < 0.001) but did not show any relation with chitotriosidase ( P = 0.546). FMD% decreased in patients ( P < 0.001) also showing no relation with chitotriosidase ( P = 0.298). Ventricular myocardial performance indexes had no significant difference, but RVEF% decreased in patients ( P = 0.043). Conclusions: High chitotriosidase activity in common variable immunodeficiency patients demonstrated in vivo the presence of activated macrophages indicating ongoing inflammation. Echocardiographic diastolic functional deficiency, increased cIMT and decreased FMD% may be accepted as early atherosclerotic findings, but none of them showed relationship with chitotriosidase activities.